Fetal growth, birth size and energetic cost of gestation in southern right whales. (5th April 2022) - Christiansen, Fredrik; Uhart, Marcela M; Bejder, Lars; Clapham, Phil; Ivashchenko, Yulia; Tormosov, Dmitry; Lewin, Nicolás; Sironi, Mariano
Abstract : Abstract: The cost of reproduction greatly affects a species' life history strategy. Baleen whales exhibit some of the fastest offspring growth rates in the animal kingdom. We quantified the energetic cost of gestation for southern right whales ( Eubalaena australis ) by combining whaling catch records of pregnant females with photogrammetry data on southern right whale mothers and calves from two breeding grounds in Argentina and Australia. The relationship between calf birth size and maternal length was determined from repeated measurements of individual females before and after giving birth. Fetal growth was determined from generalized linear models fitted to fetal length data from whaling operations between 1961 and 1967. Fetal length was converted to volume and mass, using the volume‐to‐length relationship of newborn southern right whales calves, and published tissue composition and energy content estimates. Fetal maintenance costs (heat of gestation) and the energy content of the placenta were predicted from published relationships and added to the fetal growth cost to calculate the total cost of gestation. Our findings showed that fetal growth rates and birth size increased linearly with maternal length, with calves being born at ∼35% maternal length. Fetal length increased curvilinearly through gestation, which resulted in an exponential increase in fetal volume and mass. Consequently, the cost of gestation was very low during the first (0.1% of total cost) and second trimester (4.9%), but increased rapidly during the last trimester (95.0%). The heat of gestation incurred the highest cost for pregnant females (73.8%), followed by fetal growth (21.2%) and the placental energy content (5.0%). Key points: Baleen whales exhibit some of the fastest fetal growth rates in the animal kingdom. Despite this, the energetic cost of gestation is largely unknown, as well as the influence of maternal body size on fetal growth rates and calf birth sizes. We combined historical whaling records and drone photogrammetry data to determine fetal growth rates and birth sizes in southern right whales ( Eubalaena australis ), from which we estimated the cost of gestation. Calf birth size, and consequent fetal growth rates, increased positively with maternal body size. The cost of gestation was negligible for southern right whale females during the first two trimesters, but increased rapidly during the last trimester. These results show that late gestation incurs a significant cost for baleen whale females, and needs to be accounted for in bioenergetic models. Abstract : Abstract figure legend The aim of this study was to estimate the energetic cost of gestation in southern right whales. First, drone photogrammetry was used to measure the size of newborn southern right whale calves on their breeding grounds. Birth lengths were found to be ∼35% of maternal lengths. Based on this, fetal growth curves were developed from historical whaling records. The fetus grew slowly in size during the first two trimesters, but increased rapidly during the final trimester. The growth rate of the fetus was positively affected by the size (length) of the mother, with larger females having faster growing fetuses. By converting fetal length to volume and mass, and using the energetic content of different tissues (blubber, muscle, viscera and bones), the cost of fetal growth through gestation could be estimated. Placental cost and heat of gestation were calculated from the fetal size, which together equalled the cost of gestation.